MANual : the body builder's manual. (Washington : MANual Enterprises Inc., 1959)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks
Redactie : Box 385, Bejamin Franklin Station, Washington 4 DC
Engels
Periodiek